One-dimensional cerium-based metal halide perovskite crystal and preparation method and application thereof
By developing one-dimensional cerium-based metal halide perovskite crystal Cs3CeCl6·3H2O, the problem of insufficient exploration of high-dimensional structure in the prior art was solved, efficient photoluminescence and high structural dimensions were achieved, and a wide range of application prospects for optoelectronic devices were achieved.
Patent Information
- Application Number
- CN202411908142.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
There is a lack of efficient luminescent compounds that can independently assemble lanthanide ions in the prior art, and metal halides based on lanthanides tend to form zero-dimensional structures, and relatively few explorations of high-dimensional structures limit the photoelectric properties and structural dimensions of the material.
A one-dimensional cerium-based metal halide perovskite crystal Cs3CeCl6·3H2O was developed, including nanocrystalline and single crystal form. The preparation of this material was achieved through a specific synthesis method, with a unique anionic layer structure and high photoelectric quality.
It has achieved photoluminescence quantum yield up to 100%, with huge luminescence efficiency and photoelectric performance potential, and is suitable for the field of optoelectronic devices.
Smart Images

Figure CN119753836A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic chemical synthesis, and in particular relates to a one-dimensional cerium-based metal halide perovskite crystal and a preparation method and application thereof. Background Art
[0002] In the field of optoelectronic materials, perovskite nanocrystals have attracted much attention due to their unique optoelectronic properties, especially in applications such as light-emitting diodes (LEDs), lasers, and photodetectors. Lanthanide-based metal halides, as a new type of lead-free perovskite material, have become a hot topic of research due to their efficient luminescence performance and ability to emit light at multiple wavelengths. These materials exhibit sharp and well-defined emission peaks in the ultraviolet (UV) to mid-infrared range and high photoluminescence quantum yields (PLQY) close to 1, which makes them have great application potential in the optoelectronic field.
[0003] The remarkable luminescence performance of perovskite derivatives can be attributed to the screening effect of lanthanide ions, which is promoted by the filled 5S2 and 5P6 orbitals, allowing the materials to emit narrow-band light that is relatively unaffected by external factors. In addition, the efficient photoexcitation process of halogen ions can provide sufficient electrons to lanthanide ions, resulting in an overall increase in the luminescence energy level. Despite the promising prospects of lanthanide-based halides, there is a lack of luminescent compounds that can independently assemble lanthanide ions. Most lanthanide-based metal halides tend to form zero-dimensional lanthanide-halogen molecule polyhedral networks, while high-dimensional structures (such as one-dimensional, two-dimensional or three-dimensional) are relatively less explored. In the study of lead, antimony (Sb) and copper (Cu) metal halides, the structural dimensions of the crystals are affected by the local coordination environment and the non-covalent interactions between the metal halide polyhedra, which also depends on the specific synthesis environment. Achieving high structural dimensionality is crucial to obtain the high electronic dimensionality required for efficient carriers. Therefore, the development of lanthanide-based materials with high optoelectronic quality and high structural dimensionality is of great significance to promote the advancement of environmentally friendly optoelectronic technologies. Summary of the invention
[0004] The present invention aims to provide a one-dimensional cerium-based metal halide perovskite crystal and a preparation method and application thereof. The crystal has high photoelectric quality and high structural dimension and has broad application prospects in the field of optoelectronic devices.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A one-dimensional cerium-based metal halide perovskite crystal, wherein the crystal is Cs3CeCl6·3H2O and includes two forms: nanocrystal and single crystal.
[0007] The present invention also provides a method for preparing Cs3CeCl6·3H2O nanocrystals, comprising the following steps:
[0008] S1, adding Cs2CO3 and Ce(OAc)3·xH2O to a mixture consisting of octadecene, oleic acid and oleylamine to obtain a reaction mixture A;
[0009] S2, heating the reaction mixture A obtained in step S1 to 120° C. for 1 h under vacuum, and continuing to heat to 210° C. under N2 atmosphere, rapidly injecting trimethylsilyl chloride, reacting for 2 min, placing in an ice-water bath, and cooling to room temperature to obtain a reaction mixture B;
[0010] S3, centrifuging the reaction mixture B obtained in step S2 at 8000 rpm for 5 min, discarding the supernatant, mixing the precipitate with hexane, ultrasonically treating, centrifuging again, discarding the precipitate, and obtaining a reaction mixture C;
[0011] S4. Add methyl acetate to the reaction mixture C obtained in step S3, mix well, centrifuge at 8000 rpm for 5 min, discard the supernatant, disperse the precipitate in hexane, centrifuge at 5000 rpm for 5 min, discard the precipitate, and obtain Cs3CeCl6·3H2O nanocrystals.
[0012] Preferably, in step S3, the ultrasonic treatment frequency is 35-45 kHz, the ultrasonic time is 2 min, the secondary centrifugation speed is 4000 rpm, and the centrifugation time is 5 min.
[0013] The invention also provides Cs3CeCl6·3H2O nanocrystals prepared by the preparation method.
[0014] The present invention also provides the Cs3CeCl6·3H2O nanocrystal prepared by the preparation method or the application of the Cs3CeCl6·3H2O nanocrystal in the luminescent material of LED device.
[0015] The present invention also provides a method for preparing a Cs3CeCl6·3H2O single crystal, comprising the following steps:
[0016] T1. Dissolve CeCl3·xH2O and Cs2CO3 in HCl and stir to obtain a mixture solution;
[0017] T2. The mixture solution obtained in step T1 was heated to 120° C. in an oil bath for 30 min, slowly cooled to room temperature, allowed to stand for 12 h, filtered under reduced pressure, washed with hexane, and dried in vacuum to obtain a Cs3CeCl6·3H2O single crystal.
[0018] Preferably, the vacuum drying temperature in step T2 is 60° C. and the drying time is 24 h.
[0019] The invention also provides a Cs3CeCl6·3H2O single crystal prepared by the preparation method.
[0020] The present invention also provides a Cs3CeCl6·3H2O single crystal prepared by the preparation method or an application of the Cs3CeCl6·3H2O single crystal in an X-ray scintillator.
[0021] Compared with the prior art, the present invention has the following advantages and technical effects:
[0022] The present invention discloses a one-dimensional cerium-based metal halide perovskite crystal, which is Cs3CeCl6·3H2O, including two forms of nanocrystal and single crystal, and has a unique anion layer structure, which is composed of tetradecahedral units connected by H2O-Ce-Cl bonds. The Cs3CeCl6·3H2O conduction band bottom is increased due to the increase in the structural size, so that the material can achieve effective electrical injection. For Cs3CeCl6·3H2O single crystal and nanocrystal, from Cl - To Ce 3+ Or directly Ce 3+ When ions 4f-5d are excited, a photoluminescence quantum yield of up to 100% is achieved, which has great potential in terms of luminescence efficiency and optoelectronic performance.
[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The application of Cs3CeCl6·3H2O single crystal in X-ray scintillator, wherein: Figure 1 (a) is the normalized integrated RL intensity of Cs3CeCl6·3H2O as a function of different X-ray doses. Figure 1 (b) is the RL spectra of Cs3CeCl6·3H2O and LuAG:Ce. Figure 1 (c) is a photo of a complete X-ray test sample of Cs3CeCl6·3H2O. Figure 1 (d) in the figure is the linear relationship between the signal-to-noise ratio (SNR) value and the X-ray dose rate measured by Cs3CeCl6·3H2O. Figure 1 (e) in the figure shows the variation of PL intensity of the scintillator with thickness. Figure 1 (f) is a schematic diagram of the homemade X-ray imaging system;
[0025] Figure 2 The LED device is prepared using Cs3CeCl6·3H2O nanocrystals, wherein: Figure 2 (a) is a schematic diagram of an LED device. Figure 2(b) is the energy level diagram of the device structure. Figure 2 (c) shows the EL spectra of the best LED under different bias voltages (effective area: 0.36 cm 2 ), Figure 2 (d) in the figure is the chromaticity coordinate of the LED working at 10V bias in the corresponding device photo. Figure 2 (e) in the figure is the JVL characteristic. Figure 2 (f) in the figure is the continuous wave EQE of the LED device;
[0026] Figure 3 is the appearance of perovskite crystal, where Figure 3 (a) is a photo of a nanocrystal solution taken under ambient light and 334nm UV light. Figure 3 (b) is the XRD pattern of the prepared nanocrystals and single crystals, and the inset is a photo of the single crystal taken under ambient light and 334nm UV light. Figure 3 (c) is the crystal structure of Cs3CeCl6·3H2O created by VESTA software. Figure 3 (d) is the TG-DSC curve of Cs3CeCl6·3H2O single crystal. Figure 3 (e) is the TEM image of the synthesized Cs3CeCl6·3H2O NC. Figure 3 (f) is the STEM-EDS plot;
[0027] Figure 4 is the spectrum test result of the crystal, where Figure 4 (a) is the UV-absorption spectrum of Cs3CeCl6·3H2O nanocrystals and single crystals, and the inset is the Tauc plot of NC. Figure 4 (b) is the PL spectrum. Figure 4 (c) is the PLE spectrum. Figure 4 (d) is the PL peak intensity as a function of temperature. Figure 4 (e) is the TRPL decay curve of the nanocrystal. Figure 4 (f) in the figure is the TRPL decay curve of the single crystal;
[0028] Figure 5 is the theoretical calculation result of crystal luminescence mechanism, where: Figure 5 (a) is the band structure and PDOS of Cs3CeCl6·3H2O. Figure 5 The left and right parts of (b) are partial charge density diagrams of VBM and CBM respectively. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0030] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0031] In the present invention, unless otherwise specified, other test materials and instruments and equipment are conventional test materials in the art and can be purchased through commercial channels.
[0032] Embodiment 1 This embodiment provides a Cs3CeCl6·3H2O nanocrystal, and the preparation method comprises the following steps:
[0033] S1. 0.125 mmol Cs2CO3 and 0.25 mmol Ce(OAc)3·xH2O were added to a mixture consisting of 5 mL octadecene, 1.25 mL oleic acid and 0.33 mL oleylamine to obtain a reaction mixture A;
[0034] S2, heating the reaction mixture A obtained in step S1 to 120° C. for 1 h under vacuum, heating the reaction mixture to 210° C. under N2 atmosphere, rapidly injecting 400 μL of trimethylsilyl chloride, reacting for 2 min, placing in an ice-water bath, and cooling to room temperature to obtain a reaction mixture B;
[0035] S3, decant the reaction mixture B obtained in step S2 into a centrifuge tube, centrifuge at 8000 rpm for 5 min, discard the supernatant, mix the precipitate with 5 mL of hexane, perform ultrasonic treatment at 40 kHz for 2 min, centrifuge again at 4000 rpm for 5 min, discard the precipitate, and obtain a reaction mixture C;
[0036] S4. Add 5 mL of methyl acetate to the reaction mixture C obtained in step S3, mix well, centrifuge at 8000 rpm for 5 min, discard the supernatant, disperse the precipitate in 5 mL of hexane, centrifuge at 5000 rpm for 5 min, discard the precipitate, and obtain Cs3CeCl6·3H2O nanocrystals.
[0037] Embodiment 2 This embodiment provides a Cs3CeCl6·3H2O single crystal, and the preparation method comprises the following steps:
[0038] T1. Dissolve 1 mmol CeCl3·xH2O and 1.5 mmol Cs2CO3 in 1 mL HCl and stir to obtain a mixture solution;
[0039] T2. The mixture solution obtained in step T1 was heated to 120° C. in an oil bath for 30 min, slowly cooled to room temperature, allowed to stand for 12 h, filtered under reduced pressure, washed with hexane, and dried under vacuum at 60° C. for 24 h to obtain a Cs3CeCl6·3H2O single crystal.
[0040] The effects of the above embodiments are verified by the following experiments.
[0041] X-ray scintillator:
[0042] Imaging camera: A miniature X-ray tube is used as the X-ray source, producing an X-ray output spectrum with both strong characteristic radiation of silver and a wide range of bremsstrahlung radiation. The average X-ray photon energy is 22keV.
[0043] X-ray imaging description: A Mini-X X-ray tube was used as the X-ray source, producing an X-ray output spectrum with strong characteristic radiation of Ag and broad bremsstrahlung. The average X-ray photon energy was about 22keV. The X-ray dose rate was calibrated with a high-sensitivity X-ray ionization chamber dosimeter. The object and scintillator wafer were placed perpendicular to the incident X-rays, and the scintillator was fixed behind the object. A reflector was used to deflect the light path by 90° to reduce the negative impact of direct radiation from the X-ray source on the camera. A CMOS camera was equipped to collect X-ray images.
[0044] X-ray radiation light yield test: Place the test sample and standard sample in front of the integrating sphere, and the X-ray source in front of the sample. While ensuring equal X-ray absorption, the integrating sphere and FLS 1000 spectrometer are connected in series through optical fiber. The light yield is calculated by comparing the integrated area of sample A and LuAG:Ce (LY: 22000Ph / MeV).
[0045] Film preparation: Grind the sample evenly, then mix it evenly with PDMS, and prepare a film with uniform thickness by scraping.
[0046] LED device preparation:
[0047] The ITO-coated glass substrate was rinsed with deionized water and then ultrasonically treated in deionized water, acetone, and isopropanol for 15 min, respectively. The substrate was then dried at 125 ± 5 °C for 10 min and treated with UV ozone for 10 min before use. Thereafter, a PEDOT:PSS aqueous solution filtered through a 0.22 μm PTFE filter was spin-coated on the pre-cleaned ITO glass at 4500 rpm for 40 s and then annealed at 125 ± 5 °C for 30 min under ambient conditions. The hole transport layer was prepared by dissolving 8 mg PVK and 2 mg TCTA in 1 mL chlorobenzene solution and then spin-coated on the PEDOT:PSS layer at 4000 rpm for 30 s, followed by annealing at 150 °C for 30 min in a glove box. Subsequently, a colloidal suspension of Cs3CeCl6·3H2O nanocrystals (20 mg / mL in octane) was spin-coated on the PVK / TCTA layer at 3600 rpm for 30 s, and then a 40 nm thick TPBi layer was deposited using a vacuum thermal evaporator. Finally, the cathode was fabricated by thermally evaporating a LiF layer (1.0 nm) followed by an Al layer (100 nm). Each substrate was patterned to realize three devices, each with a 0.36 cm 2 All devices were stored and characterized in ambient atmosphere without packaging.
[0048] Figure 1 (a) shows the monotonically increasing X-ray stimulated radioluminescence (RL) intensity of the screen, which is linearly related to the X-ray dose rate. Figure 1 (b) By comparing the X-ray absorption of Cs3CeCl6·3H2O with the reference LuAG:Ce and the corresponding RL spectrum, the steady-state light yield of Cs3CeCl6·3H2O was determined to be 31900photons / MeV, which is higher than LuAG:Ce (22000photons / MeV) and CsPbBr 3 (21000photons / MeV). Figure 1 (c) In order to evaluate the spatial resolution of the screen, an X-ray image of a standard resolution test template was acquired. Compared with its bright field image, the resolution limit can be observed at 10-12 lp / mm. Figure 1 (d) in Figure 3 determined a detection limit of 0.108 μGy / s, which is lower than the detection limit of LuAG:Ce (2.32 μGy / s) and 50 times lower than the standard dose used for X-ray diagnosis (5.5 μGy / s). Figure 1 (e) shows the thickness-dependent RL intensity. At different thicknesses, the RL intensity of Cs3CeCl6·3H2O exceeds that of LuAG:Ce, thus rationalizing its superior superior scintillator performance. Figure 1(f) An X-ray image of a metal key was obtained using a homemade imaging system using a Cs3CeCl6·3H2O screen, showing the X-ray image of the key acquired at a voltage of 50 kV and a dose rate of 16.4 μGy / s.
[0049] Depend on Figure 2 The device structure used in (a) is ITO / PEDOT:PSS / PVK+TCTA / NC / TPBi / LiF / Al. Figure 2 (b) shows the arrangement of energy levels. Figure 2 (c) shows the EL spectra of the LED at various applied biases ranging from 8 to 14 V, which reveals a peak position at 380 nm attributed to Ce. 3+ However, in addition to the Ce emission in the wavelength range of 350 to 450 nm 3+ In addition to the violet emission, a relatively weak parasitic broadband emission spanning 500 to 800 nm is also observed, implying that electrons and holes can also recombine via pathways just beyond the NC layer. Figure 2 (d) in the figure is the chromaticity diagram of the device corresponding to the spectral result, which shows that there is a certain deviation between the chromaticity coordinates of the LED light and the fluorescence chromaticity coordinates of the pure NC. Figure 2 The inset of (d) shows a typical photograph of the fabricated LED operated at a bias of 10 V. In the image, non-uniform violet emission is evident, which may originate from the non-uniform contact between the various transport layers. Figure 2 (e) and Figure 2 (f) shows the current-voltage-luminance (JVL) characteristics and continuous wave external quantum efficiency (EQE) curve of the LED. The turn-on voltage required for the LED device (in lcd / m 2 The maximum brightness of the LED display is about 2.3cd / m 2 , EQE is 0.13%.
[0050] Depend on Figure 3 As shown in (a), under 334nm ultraviolet light, the nanocrystals show bright purple emission, characterized by chromaticity coordinates of (0.17, 0.01) and a correlated color temperature of about 1939K. Figure 3As can be seen from (b) in the figure, the crystal structure of the obtained nanocrystals is first checked by powder X-ray diffraction (XRD) measurement. The diffraction pattern shown by the nanocrystals cannot be attributed to any known crystal structure, that is, a new crystal structure is obtained. In order to determine the crystal structure, SC is synthesized by a cooling-induced crystallization process. Single crystal X-ray diffraction analysis shows that the chemical composition of the crystal is Cs3CeCl6·3H2O. The XRD spectrum of the single crystal is in good agreement with the XRD spectrum of the nanocrystals. The chemical composition of the synthesized nanomaterial is Cs3CeCl6·3H2O, which belongs to the orthorhombic crystal system and has a space group of Pnma. Figure 3 As shown in (c), each H2O-Ce-Cl tetradecahedron is connected to adjacent units through edge sharing, forming a network that is tightly connected in one direction. This 1D connectivity is not common in other Ln 3+ It is rare in the metal halides; even in the recently reported Bi 3+ , Sb 3+ 、In 3+ and Ag + In the case of NCs, they also usually have a 0D structure. The results show that the synthesis method of this patent is very different from the existing synthesis methods, especially in terms of the ratio of precursor reactants and the concentration of organic ligands. These parameters are crucial in generating a one-dimensional crystal structure because they can affect the crystallization kinetics of NCs. The thermal stability of the crystals was evaluated by thermogravimetric and differential scanning calorimetry (TGDSC) analysis. Figure 3 As can be seen from (d) in Figure 1, an initial weight loss of about 16% occurs at about 150°C, which is attributed to the removal of coordinated water. Figure 3 As shown in (e), the transmission electron microscopy (TEM) image shown in Figure 3 shows that the Cs3CeCl6·3H2O nanocrystals are almost monodisperse, showing a hexagonal shape with an average diameter of 1.21 nm. In addition, the clear lattice fringes observed in the high-resolution TEM image indicate that the nanocrystals have high crystallinity. Figure 3 As can be seen in (f), uniform distribution of Cs, Ce, Cl and O elements in NC was observed by scanning TEM energy dispersive X-ray spectroscopy (STEM-EDS) mapping.
[0051] Depend on Figure 4 As shown in (a) in Figure 1, the UV-absorption spectrum of NC shows a very strong and sharp absorption at 350nm, which is almost parallel to the absorption axis, indicating direct band edge absorption, from which a band gap value of 3.51eV can be derived. Figure 4 (b) and Figure 4 As shown in (c), the PL (excitation) spectrum was recorded at 334 nm and the emission (PLE) spectrum was recorded at 373 nm. Figure 4As shown in (d) above, the temperature-dependent integrated PL intensity can be fitted using the Arrhenius equation as follows:
[0052]
[0053] where I(T) is the integrated PL intensity at T(K), A is a constant, and kB is the Boltzmann constant. The results show that the Eb value of Cs3CeCl6·3H2O is 23.6meV, which is close to the thermal perturbation energy (26meV) at 300K, but significantly smaller than the binding energy of 0D metal halides, specifically, it is even lower than the value of 135meV observed in Cs3CeBr6. This is due to the one-dimensional chain structure of Cs3CeCl6·3H2O, which weakens the confinement of excitons. In order to study the recombination of carriers in the crystal, time-resolved PL (TRPL) measurements were performed. By Figure 4 (e) and Figure 4 As can be seen from (f) in the figure, the recorded PL decay dynamics of nanocrystals and single crystals follow single exponential statistics, with decay lifetimes of 1.32 and 35 ns, respectively, indicating the absence of non-radiative pathways, which is consistent with their high PLQY.
[0054] Depend on Figure 5 As shown in (a), in order to better study the luminescence properties of Cs3CeCl6·3H2O, density functional theory (DFT) was used to further study their electronic structure. The valence band (VB) state of Cs3CeCl6·3H2O has an almost flat and highly discrete energy band, indicating that the intermolecular coupling is extremely small, which is typical in low-dimensional metal halides. This behavior originates from the fact that Cs + The spatial isolation of ion-paired H2O-Ce-Cl tetrahedra leads to obvious quantum confinement of photoexcited holes. On the other hand, the CBM of Cs3CeCl6·3H2O exhibits enhanced dispersion properties compared with 0D Cs3CeBr6. This enhancement can be attributed to the unique 1D structure of Cs3CeCl6·3H2O, which enables injected or photogenerated electrons to move in a 1D manner. The orbital projected density of states (PDOS) shows that the VB maximum (VBM) of Cs3CeCl6·3H2O is mainly composed of Cl-p and Ce-f orbitals, whose charges are distributed around Cl and Ce atoms, respectively, as shown in Figure 2. Figure 5 The partial charge density plotted in (b) is shown in Figure 3. The charge of the Ce-d orbital, which mainly contributes to the CBM, is distributed around the H2O-Ce-Cl tetradecahedron. This shows that the energy band edge of Cs3CeCl6·3H2O is mainly determined by the H2O-Ce-Cl tetradecahedron, and there are two transition modes: the transition between the energy states Cl-p and Ce-d and the transition between Ce-f and Ce-d. These energy levels are reasonably consistent with the PLE spectrum.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A one-dimensional cerium-based metal halide perovskite crystal, characterized in that: The crystal is Cs3CeCl6·3H2O, including two forms: nanocrystal and single crystal.
2. A method for preparing Cs3CeCl6·3H2O nanocrystals, characterized in that: The steps include: S1, adding Cs2CO3 and Ce(OAc)3·xH2O to a mixture consisting of octadecene, oleic acid and oleylamine to obtain a reaction mixture A; S2, heating the reaction mixture A obtained in step S1 to 120° C. for 1 h under vacuum, and continuing to heat to 210° C. under N2 atmosphere, rapidly injecting trimethylsilyl chloride, reacting for 2 min, placing in an ice-water bath, and cooling to room temperature to obtain a reaction mixture B; S3, centrifuging the reaction mixture B obtained in step S2 at 8000 rpm for 5 min, discarding the supernatant, mixing the precipitate with hexane, ultrasonically treating, centrifuging again, discarding the precipitate, and obtaining a reaction mixture C; S4. Add methyl acetate to the reaction mixture C obtained in step S3, mix well, centrifuge at 8000 rpm for 5 min, discard the supernatant, disperse the precipitate in hexane, centrifuge at 5000 rpm for 5 min, discard the precipitate, and obtain Cs3CeCl6·3H2O nanocrystals.
3. The preparation method according to claim 2, characterized in that: In step S3, the ultrasonic treatment frequency is 35-45kHz, the ultrasonic time is 2min, the secondary centrifugation speed is 4000rpm, and the centrifugation time is 5min.
4. Cs3CeCl6·3H2O nanocrystals prepared by the preparation method according to any one of claims 2 to 3.
5. Use of the Cs3CeCl6·3H2O nanocrystals prepared by the preparation method according to any one of claims 2 to 3 or the Cs3CeCl6·3H2O nanocrystals according to claim 4 in the luminescent materials of LED devices.
6. A method for preparing a Cs3CeCl6·3H2O single crystal, characterized in that: The method comprises the following steps: T1. Dissolve CeCl3·xH2O and Cs2CO3 in HCl and stir to obtain a mixture solution; T2. The mixture solution obtained in step T1 was heated to 120° C. in an oil bath for 30 min, slowly cooled to room temperature, allowed to stand for 12 h, filtered under reduced pressure, washed with hexane, and dried in vacuum to obtain a Cs3CeCl6·3H2O single crystal.
7. The preparation method according to claim 6, characterized in that: The vacuum drying temperature in step T2 is 60° C. and the drying time is 24 h.
8. Cs3CeCl6·3H2O single crystal prepared by the preparation method according to claim 6 or 7.
9. Use of the Cs3CeCl6·3H2O single crystal prepared by the preparation method according to claim 6 or 7 or the Cs3CeCl6·3H2O single crystal according to claim 8 in an X-ray scintillator.
Citation Information
Patent Citations
Halide Scintillator for Radiation Detection
CN106433645A
Cerium-doped glass matrix-based halide perovskite nanocrystalline material and preparation method thereof
CN113293435A
Perovskite CsPbX3 nanocrystal as well as preparation method and application thereof
CN113846373A
Novel lanthanide family lead-free perovskite nanocrystalline material and preparation method and application thereof
CN114410303A
Preparation method of one-dimensional organic-inorganic hybrid halide perovskite nanorod
CN118324768A